Knowledge of Nursing Personnel of the Świętokrzyskie Voivodeship Hospitals on Nosocomial Infections - Wrześniewska, Marzena; Gruszka, Jakub; Komar-Gruszka, Karolina; Bąk, Beata; Adamczyk-Gruszka, Olga (Journal of Education, Health and Sport, 2020)
Introduction: Nosocomial (also known as hospital-acquired) infections are understood as infections which develop during patient’s stay in hospital, but are not the direct cause of hospitalisation. The aim of the study: The purpose of the paper was to determine the knowledge of the nursing personnel from Świętokrzyskie Voivodeship onnosocomial infections, prevention and methods of combating them. Other addressed issues included the analysis of the work yeas and education level as related to the state of nurses' knowledge on nosocomial infections, and what are the reasons for insufficient prevention of diseases. Material and methods: The study included 208 nurses from Świętokrzyskie Voivodeship. Out of 208 questionnaires, 180 were completed correctly, the remaining 28 were answered incorrectly or incompletely, which resulted in their rejection. The statistical analysis was conducted using the Pearson Chi-squared method, with the significance level p>0.01 assumed to be insignificant. The study involved 124 women and 56 men. The youngest respondent was 23 years old and the oldest was 59 years old. There were 36 respondents below 30 years of age(20%), 88 in the 31-40 age group (48.9%), 56 in the 41-60 age group (31.1%). Results 1. The knowledge of the intermediate personnel about hospital-acquired infections is satisfactory. 2. Job seniority is not statistically significant with regard to the knowledge level on nosocomial infections. 3. The research revealeda statistically significant correlation between the knowledge level of the secondary staff and their education. 4. The study results show that the most common causes of insufficient knowledge on preventing hospital-acquired infections are staff shortages and inadequatefinancial resources.